Stakeholder Views of the Proposed Introduction of Next Generation Sequencing into the Cystic Fibrosis Screening Protocol in England - Pru Holder; Corinna C. Clark; Louise Moody; Felicity K. Boardman; Jacqui Cowlard; Lorna Allen; Claire Walter; James R. Bonham; Jane Chudleigh (MDPI AG, 2024)
The project aimed to gather, analyse, and compare the views of stakeholders about the proposed UK cystic fibrosis (CF) screening protocol incorporating next generation sequencing (NGS). The study design was based on principles of Q-methodology with a willingness-to-pay exercise. Participants were recruited from 12 CF centres in the UK. The study contained twenty-eight adults who have experience with CF (parents of children with CF (n = 21), including parents of children with CF transmembrane conductance regulator (CFTR)-related metabolic syndrome (CRMS)/CF screen positive-inconclusive diagnosis (CFSPID), an uncertain outcome (n = 3), and adults with CF (n = 4)), and nine health professionals involved in caring for children with CF. Parents and health professionals expressed a preference for a sensitive approach to NGS. This was influenced by the importance participants placed on not missing any children with CF via screening and the balance of harm between missing a case of CF compared to picking up more children with an uncertain outcome (CRMS/CFSPID). Given the preference for a sensitive approach, the need for adequate explanations about potential outcomes including uncertainty (CFSPID) at the time of screening was emphasized. More research is needed to inform definitive guidelines for managing children with an uncertain outcome following CF screening.